Efeito de diferentes concentrações salivares de glicose em biofilmes de Candida albicans e Streptococcus mutans - Brito, Arella Cristina Muniz (2019)
Diabetic individuals may present oral manifestations due to high glucose levels, that favors the development of more pathogenic biofilms in the presence of microorganisms such as Candida albicans and Streptococcus mutans. The aim of the study was analyze the effect of different glucose levels simulating different salivary conditions in C. albicans (ATCC 90028) and S. mutans (UA159) duoespecies biofilms in acrylic resins. Initially, a salivary film was developed and standardized or absorbed 600nm. Then, the biofilm cells were cultured for 96 hours on acrylic resin samples. They were subjected to constant exposures of glucose equivalent to 0, 20, 60 and 100 mM salivary levels and were in contact with 10% sucrose three times daily. Colony forming units (CFU / mL), soluble and insoluble extracellular polysaccharides (SEPS and IEPS), biomass, total protein (TP), phospholipase activity and fluorescence morphology analysis were performed. The acidogenicity of the culture medium was also measured. Data were analyzed by ANOVA / Tukey and Kruskal-Wallis / Mann-Whitney (α= 5%). The CFU / mL result for C. albicans determines media between 8.50 ± 0.23 and 8.97 ± 0.24, with significant difference between groups p <0.00. For the S. mutans count, there was a difference between 0 and 20mM (p <0.01). The other variables showed no differences between them (p> 0.05). Regarding PECs, wet weight and phospholipase production without differences (p> 0.05), despite the high proteolytic activity. For IEPS, there were differences between the 20 and 60 mM groups (p <0.01). For the TP test, there were differences between minor and major. Regarding morphology, collocalization between species was observed. The culture medium maintains acid throughout the days of use (5.6 ± 0.5). We conclude that glucose from salivary levels may interfere in the pathogenicity of C. albicans and S. mutans biofilms in acrylic resin substrates.